Apakah Regiulitas Memoderasi Keputusan Nasabah Bank Syariah - Selfi Afriani Gultom; Saparuddin Siregar; Sugianto Sugianto (Jurnal Ilmiah Ekonomi Islam, 2022)
This article is meaned to analyze the factors of service quality, product quality and promotion of the choice as a sharia bank customer by combining the moderating variable, namely religiosity. The research population is the customer of Bank Syariah Indonesia in the city of Medan. Determination of the sample is done by random method and set the number of only 100 people because of the large population, the range is too wide and the population is uniform so that it can be represented by others. The instrument of data collection was done by distributing questionnaires. Furthermore, data analysis with SEM-PLS. The results showed that service quality, product quality and promotion had a significant effect on the decision to become a customer of a sharia bank but religiosity was not able to moderate services, products and promotions on the decision to become a customer. The level of religiosity of Muslims is not an indicator for choosing to become a customer of a sharia bank. The implication of this research is that policies on Islamic banking continue to improve service quality because all banking customers without being influenced by religiosity are very happy to get the best service from banks. Islamic banks must continue to innovate on Islamic bank products that can make it easier for customers to transact regardless of customer religiosity. Islamic banks must continue to carry out best promotions to all public.